2021
DOI: 10.3389/fmed.2021.717602
|View full text |Cite
|
Sign up to set email alerts
|

ROCK1 Mediates Retinal Glial Cell Migration Promoted by Acrolein

Abstract: Objective: Acrolein is a highly reactive aldehyde that covalently binds to cellular macromolecules and subsequently modulates cellular function. Our previous study demonstrated that acrolein induces glial cell migration, a pathological hallmark of diabetic retinopathy; however, the detailed cellular mechanism remains unclear. The purpose of this study was to investigate the role of acrolein in retinal glial cell migration by focusing on rho-associated coiled-coil-containing protein kinases (ROCKs).Methods: Imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 23 publications
0
6
0
Order By: Relevance
“…ROCK1 is mainly distributed in peripheral tissues such as the lung, liver, and spleen, and ROCK2 is mainly distributed in the heart and nervous system (Yan et al, 2019 ). Recently, a study reported that ROCK1 mediates the migration of glial cells promoted by acrolein (Fukutsu et al, 2021 ). Although RNA‐Seq results and our previous acrolein‐conjucated proteomics data indicated that ROCK pathway might be involved in acrolein toxicity.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…ROCK1 is mainly distributed in peripheral tissues such as the lung, liver, and spleen, and ROCK2 is mainly distributed in the heart and nervous system (Yan et al, 2019 ). Recently, a study reported that ROCK1 mediates the migration of glial cells promoted by acrolein (Fukutsu et al, 2021 ). Although RNA‐Seq results and our previous acrolein‐conjucated proteomics data indicated that ROCK pathway might be involved in acrolein toxicity.…”
Section: Resultsmentioning
confidence: 99%
“…Recent studies indicated that ROCK2 is a promising therapeutic target for AD (Cai et al, 2021 ; Weber & Herskowitz, 2021 ). Some studies indicated that acrolein is closely related to ROCK1 (Fukutsu et al, 2021 ) but no relevant biological experiment conducted to substantiate the relationship between acrolein‐induced early AD and ROCK2 in the brain. In this study, acrolein could activate the RhoA/ROCK2/p‐cofilin pathway both in vivo and vitro (Figure 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…Of course, acrolein-dependent oxidative stress has further molecular targets. Other factors that are not without significance in diabetes and the accompanying DN, DR, and neurodegeneration include acrolein-dependent chronic inflammation, damage to blood vessels, the dysfunction of Müller cells, and the effect on cell division and proliferation [ 80 , 81 , 82 , 83 ].…”
Section: Acrolein In the Pathogenesis Of Diabetesmentioning
confidence: 99%
“…Valuable information on acrolein-dependent glial cell migration and the pathological hallmark of diabetic retinopathy is provided by the latest research from the research team of Fukutsu et al [ 80 , 118 ]. In their research on rat retinal Müller glial cell line TR-MUL5, they focused on the key retinal glial cell migration and activation of rho-associated coiled-coil-containing protein kinases (ROCKs) [ 80 , 118 ]. Activation of the ROCK-1 signaling pathway induces, among others, focal vascular constrictions, endoluminal blebbing, and subsequent retinal hypoxia [ 119 ].…”
Section: Acrolein In the Pathogenesis Of Diabetesmentioning
confidence: 99%
See 1 more Smart Citation